Association between a novel inflammation-lipid composite marker CRP/HDL and erectile dysfunction: evidence from a large national cross-sectional study - Mei, Yangyang; Chen, Yiming; Zhang, Bo; Xia, Wei; Shao, Naiyuan; Feng, Xingliang (Frontiers in Endocrinology, 2024)
Background: Erectile dysfunction (ED) is one of the most common male sexual disorders, closely associated with both inflammation and lipid dysregulation. Recently, a novel inflammation-lipid composite marker, CRP/HDL, has been proposed to integrate the impact of both pathways on health, yet its relationship with ED remains unexplored. Therefore, our study aimed to investigate the potential association between the CRP/HDL ratio and ED.We utilized data from the NHANES database, known for its comprehensive and high-quality information. A total of 3,633 eligible participants from the 2001-2004 cycles were included. ED was assessed using a single-item questionnaire, while CRP and HDL were measured from blood samples. Multivariable regression analyses were performed to evaluate the association between CRP/HDL and ED after adjusting for potential confounders. Additionally, subgroup and sensitivity analyses were conducted to test the robustness of the results, and the linear trend between CRP/HDL and ED was visualized through smooth curve fitting.Results: Among the 3,633 participants, 1,027 had a history of ED. The CRP/HDL ratio was significantly higher in participants with ED compared to those without (10.53±0.69 vs. 7.43±0.35, P<0.001). In the regression analysis, a higher continuous CRP/HDL ratio was significantly associated with increased ED risk even after full adjustment (OR: 1.17, 95% CI: 1.05, 1.30; P = 0.01). Compared to Q1 of the CRP/HDL ratio, participants